(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Premessa - 2. L’atto di scelta - 3. L’intervento del Consiglio di Stato - 4. Osservazioni critiche - 5. Una lettura costituzionalmente orientata - 6. Conclusioni. The validity of the teaching of the Catholic religion in Italian public schools ABSTRACT: Catholic RE teaching in state schools of all types and at all levels is covered by the agreement amending the Lateran Concordat and the additional protocol thereto, implemented by means of Law No 121 of 25 March 1985, and the agreement between the Italian Ministry for Education and the President of the Italian Bishops’ Conference, implemented by means of Presidential Decree No 751 of 16 December 1985, as subsequently amended.